Turn of the screw - Pope, Martin, 1961-; Dear, Nick.; Bolt, Ben, 1952-; James, Henry, 1843-1916.; May, Jodhi, 1975-; Ferris, Pam.; Firth, Colin, 1960-; Sowerbutts, Joe, 1988-; Robinson, Grace; United Productions, Ltd.; Martin Pope Productions; Meridian Broadcasting; et al. ([United States] : WGBH Boston Video, 2004)
Henry James' chilling ghost tale about a governess hired by a charming bachelor to look after two young children in a grand mansion in rural England where sinister events place their lives in jeopardy.
Originally broadcast in 1999.
Special features: access to the Exxon Mobil Masterpiece theatre web site.
Jodhi May, Pam Ferris, Colin Firth, Joe Sowerbutts, Grace Robinson.
Not rated.
DVD, region 1, full screen presentation; Dolby Digital.
Closed-captioned.
Keywords: Governesses -- England -- Drama; Orphans -- England -- Drama; Ghosts -- England -- Drama; Made-for-TV movies; Video recordings for hard of hearing people